2017
DOI: 10.1111/mmi.13879
|View full text |Cite
|
Sign up to set email alerts
|

The major cellulases CBH‐1 and CBH‐2 ofNeurospora crassarely on distinct ER cargo adaptors for efficient ER‐exit

Abstract: Filamentous fungi are native secretors of lignocellulolytic enzymes and are used as protein-producing factories in the industrial biotechnology sector. Despite the importance of these organisms in industry, relatively little is known about the filamentous fungal secretory pathway or how it might be manipulated for improved protein production. Here, we use Neurospora crassa as a model filamentous fungus to interrogate the requirements for trafficking of cellulase enzymes from the endoplasmic reticulum to the Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 100 publications
1
12
0
Order By: Relevance
“…Previous work has determined the transcription factors responsible for cellulase induction (10,34), the intracellular molecule that induces cellulolytic enzymes (54), and the adaptor proteins needed for efficient exit of cellulases from the endoplasmic reticulum (ER) to the Golgi apparatus in fungi (48). Our results contribute to this body of knowledge by providing a comprehensive analysis illustrating the importance of G-protein signaling during upstream regulation of cellulose sensing and cellulase induction.…”
Section: Figmentioning
confidence: 74%
See 2 more Smart Citations
“…Previous work has determined the transcription factors responsible for cellulase induction (10,34), the intracellular molecule that induces cellulolytic enzymes (54), and the adaptor proteins needed for efficient exit of cellulases from the endoplasmic reticulum (ER) to the Golgi apparatus in fungi (48). Our results contribute to this body of knowledge by providing a comprehensive analysis illustrating the importance of G-protein signaling during upstream regulation of cellulose sensing and cellulase induction.…”
Section: Figmentioning
confidence: 74%
“…Since the proteins appear to be made in these mutant backgrounds (Fig. 1 and S3), these may affect posttranslational modifications required for the cellulase enzymes to be functional (47,48). It should be noted that since the time point selected for our study was early during cellulase induction, it is possible that levels of these mRNAs may be higher at later times after transfer to Avicel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore the fact that CG forms are markedly abundant in InuA extracted from mycelia strongly suggests that, at least for this cargo, ER exit is limiting for secretion in A. nidulans . In this particular regard we note that a recent study demonstrated that CBH‐1 and CBH‐2, the major cellulases of Neurospora crassa , use different cargo adaptors (the p24 complex and Erv29 respectively) to the COPII coat during ER exit (Starr et al, ). Future studies will address whether one or more A. nidulans cargo adaptors mediating incorporation of InuA into COPII carriers is/are limiting.…”
Section: Discussionmentioning
confidence: 93%
“…This modification is necessary for Chs3p to achieve a competent conformation required for its ER exit ( Lam et al, 2006 ). Moreover, the ER export cargo Chs7p ( Starr et al, 2018 ) is responsible for directing the appropriate folding of Chs3p, avoiding its aggregation in the ER ( Kota and Ljungdahl, 2005 , Trilla et al, 1999 ). Chs3p is then transported to Golgi.…”
Section: Behind the Scenes To A Successful Destination: The Path Of Tmentioning
confidence: 99%